Evaluation of Onion Peel as Feed Additive on Performance Production Broiler - Nurul Jannah, Saadatin; Edhy Sudjarwo; Osfar Sjofjan (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
This study evaluated the impact of adding onion (Allium cepa L.), shallot (Allium ascalonicum L.), and garlic (Allium sativum L.) peels as additives to the broiler production. The material used was 189 one-day-old commercial broiler chicken Lohmann strain (unsexing) and assigned to nine treatments and three replications: T0(-): basal diet, T0(+): basal diet + antibiotic (zinc bacitracin 0.1%), T1: basal diet + 0.5% garlic peel, T2: basal diet + 0.5% shallot peel, T3: basal diet + 0.5% onion peel, T4: basal diet + 0.25% garlic peel and 0.25% shallot peel, T5: basal diet + 0.25%. garlic peel + 0.25% onion peel, T6: basal diet + 0.25% shallot peel + 0.25% onion peel, T7: basal diet + 0.167% garlic peel + 0.167% shallot peel + 0.167% onion peel. Feed intake, final body weight, feed conversion ratio (FCR), mortality, productivity index, and income over feed cost were the variables that were observed in the current study. The data were analysed using Analysis of Variance (ANOVA). The results of the study show that the addition of the three garlic powders do not give any effect (P>0.05) on feed intake, final body weight, FCR, mortality, production index and IOFC. The conclusions of this study showed that garlic peel, shallot peel, and onion peel could be used as feed additive. This choice yields positive effects on production performance, particularly in terms of Feed Conversion Ratio (FCR) and the production index.